Breast Hypertrophy, Reduction Mammaplasty, and Body Image. (7th February 2018) - Fonseca, Cristiane Costa; Veiga, Daniela Francescato; Garcia, Edgard da Silva; Cabral, Isaías Vieira; de Carvalho, Monique Maçais; de Brito, Maria José Azevedo; Ferreira, Lydia Masako
Abstract: Background: Body image dissatisfaction is one of the major factors that motivate patients to undergo plastic surgery. However, few studies have associated body satisfaction with reduction mammaplasty. Objectives: The aim of this study was to evaluate the impact of breast hypertrophy and reduction mammaplasty on body image. Methods: Breast hypertrophy patients, with reduction mammaplasty already scheduled between June 2013 and December 2015 (mammaplasty group, MG), were prospectively evaluated through the body dysmorphic disorder examination (BDDE), body investment scale (BIS), and breast evaluation questionnaire (BEQ55) tools. Women with normal-sized breasts were also evaluated as study controls (normal-sized breast group, NSBG). All the participants were interviewed at the initial assessment and after six months. Data were analyzed before and after six months. Results: Each group consisted of 103 women. The MG group had a significant improvement in BDDE, BIS, and BEQ55 scores six months postoperatively ( P ≤ 0.001 for the three instruments), whereas the NSBG group showed no alteration in results over time ( P = 0.876; P = 0.442; and P = 0.184, respectively). In the intergroup comparison it was observed that the MG group began to invest more in the body, similarly to the NSBG group, and surpassed the level of satisfaction and body image that the women of the NSBG group had after the surgery. Conclusions: Reduction mammaplasty promoted improvement in body image of women with breast hypertrophy. Level of Evidence: 2: